Computational fluid dynamics modelling of expanded metal porous matrix heat exchangers for intensified carbon capture applications. (1st August 2022) - Hendry, James; Reay, David; Lee, Jonathan
Highlights: A computational fluid dynamics model of heat exchange in an expanded metal porous matrix heat exchanger is presented. Results are validated against experimental data from literature to within 10% error. Intercooling the rotating packed bed absorber using compact heat exchange can achieve approach temperatures of 3 °C. The CFD model also suggests an estimated 10x volume reduction for lean/rich heat exchangers in amine-based carbon-capture processes. Abstract: Expanded Metal Porous Matrix Heat Exchangers (EM-PMHE) use a fin structure based on stacked sheets of expanded metal. This fin structure creates a three-dimensional flow that also enhances heat transfer. EM-PMHEs are of interest for potential applications in carbon-capture processes. Their compact design could intensify heat exchange processes in the amine absorption cycle. The transport properties of EM-PMHEs are also of interest for applications in rotating packed beds, where expanded metal can make an effective packing material. This work examines a EM-PMHE using computational fluid dynamics. The heat transfer prediction of the model is validated against experimental data from literature. A simple 1D model is also presented for comparison. The model is used to evaluate the potential of EM-PMHEs in amine-based carbon-capture applications. The modelling results indicate that EM-PMHEs could be used to achieve intercooling in the rotating packed bed absorber. This would allow amine concentrations to be increased to 70 wt% in the carbon-capture process, achieving 2x volume reduction in comparison to conventional amine concentrations. Elsewhere in the carbon-capture process, EM-PMHEs could also achieve an 10x size reduction in the lean/rich heat exchanger, a major item of plant equipment in the carbon capture process.